2023
DOI: 10.1038/s41598-023-39713-2
|View full text |Cite
|
Sign up to set email alerts
|

Micro-mechanical and tribological behavior of Al/SiC/B4C/CNT hybrid nanocomposite

Abstract: The aluminum nanocomposite is fabricated through squeeze stir casting method where CNT, SiC/B4C powder has been used as a reinforcement in an aluminum matrix. Squeeze action in stir casting opted due to proper reinforcement of 2 vol% of CNT in the matrix. The boron carbide and silicon carbide have been added by 8 and 12 vol% in the matrix. Uniform distribution of reinforcement and phase analysis has been shown by scanning electron microscopy (SEM) and XRD analysis. The formation of intermetallic compounds like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Considering all the above mentioned, it can be conclusively found that the effect of laser energy density on the microstructure of AlSi10Mg has been studied, but few studies reported the influence of laser energy density on tribological property. As reported in the relevant research [10,15], laser energy density has a great impact on grain size and quality, which further affects the tribological property of the printed parts. So, in this work, the role of laser energy density on microstructure, density, surface roughness (Ra) and micro-hardness were also explored, given their close relationship to wear resistance.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Considering all the above mentioned, it can be conclusively found that the effect of laser energy density on the microstructure of AlSi10Mg has been studied, but few studies reported the influence of laser energy density on tribological property. As reported in the relevant research [10,15], laser energy density has a great impact on grain size and quality, which further affects the tribological property of the printed parts. So, in this work, the role of laser energy density on microstructure, density, surface roughness (Ra) and micro-hardness were also explored, given their close relationship to wear resistance.…”
Section: Introductionmentioning
confidence: 97%
“…It is also worth noting that tribological property is extremely important in practice since it is considered as one of the most important factors in determining the service life of the printed part, and it has been reported in recent research [9][10][11][12]. Mishra et al [13] investigated the anti-wear performance of SLM-manufactured AlSi10Mg with different scan strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of materials undergo remarkable changes when they are processed to the nanometre scale. These changes affect the chemical, electrical, mechanical, optical, thermal, magnetic, and acoustic properties 1,2 . Hence, nanomaterials have attracted significant attention in recent years in most fields, especially diagnosis and sensing devices 3,4 .…”
Section: Introductionmentioning
confidence: 99%